Inclusión educativa, habilidades diferentes y asperger - Cuzcano Zapata, Abel (2017)
Currently, in the Peruvian school system, policies that effectively support students with special needs, including students with generalized Developmental Disorders, such as children and youth with Asperger Diagnosis, are not fully complied with . The Law on Persons with Disabilities, Law No. 29973, which governs public and private institutions, indicates that all educational institutions, at all levels and modalities, must reserve at least two vacancies per classroom for students with special educational needs associated with disability (mild or moderate) and the Director must request support from SAANE (Service of support and advice to the Special Educational needs) in order to guarantee the pertinent educational attention of these students, however the reality is that in the schools In general, there is no educational inclusion program, nor institutional inclusion policies, nor adequate curricular adaptations, the staff does not have among its functions, attention to diversity.